Use of the orbital atherectomy system backed up with the guide-extension catheter for a severely tortuous calcified coronary lesion - Kobayashi, Norihiro (SAGE Open Med Case Rep, 2020)
A 68-year-old man was scheduled to undergo percutaneous coronary intervention for in-stent total occlusion of the severely tortuous right coronary artery. Intravascular ultrasound revealed heavy in-stent calcification. Lesion atherectomy was required; however, severe proximal vessel tortuosity was detected. We introduced a 7-Fr guide-extension catheter beyond the severely tortuous part and performed rotational atherectomy with a 1.5 mm burr. However, the balloon could not expand; therefore, we changed to an orbital atherectomy system. Subsequently, the balloon successfully expanded, and intravascular ultrasound revealed an enlarged lumen. Severe proximal vessel tortuosity limits the use of atherectomy devices; however, a guide-extension catheter delivers the atherectomy device beyond the tortuosity. The delivery of the orbital atherectomy system inside the guide-extension catheter is easy due to its low profile; the debulking effect increases with the number of passes and rotational speed. This strategy is a useful option for treating severe calcified lesions with proximal vessel tortuosity.